Social Movements and Politics during COVID-19 Crisis, Solidarity and Change in a Global Pandemic - Bringel, Breno; Pleyers, Geoffrey (Bristol University Press, 2022)
EPUB and EPDF available Open Access under CC-BY-NC-ND licence. Bringing together leading authors in the sociology and social movement fields from all continents, this unique book explores both the global echoes of the pandemic and the different local and national responses adopted by different actors. The authors reveal how the pandemic exacerbates inequalities across the world whilst opening up new solidarities and hopes for a better future.